PEMBERDAYAAN MASYARAKAT DI DESA WISATA MONDU KECAMATAN KANATANG KABUPATEN SUMBA TIMUR - Linda Rambu Kuba Yowi; Leonard Rihi; Dince Danga Dupa; Teto Putri Asgetri; Eunike Mita Ga; Yosua Pebryanto Blegur; Erdi Katanga Yani; Ersita Hambajawa; Jesynta Landu Natar; Yesinta Pangga Limu; Umbu Leha Kulandima (Jurnal Abdi Insani, 2023)
Real Work Lecture (KKN) is a form of community service carried out by universities. KKN activities were carried out in Mondu Village, Kanatang District, East Sumba Regency. Apart from having potential, this village also has several problems, namely several elementary and middle school students have difficulty understanding subject matter at school as a result of schooling from home which occurred during the Covid-19 pandemic, several SMEs, specially woven businesses, whose product marketing is only through selling at traditional markets and waiting for buyers to come to buy their products so that the sales turnover is small and also affected by the Covid-19 pandemic, and not all of the tourist objects in Mondu Village are known to the wider community. Therefore, the KKN program that is carried out is tutoring students, introducing social media for woven craftsmen, and making videos of tourist attractions in Mondu Village. The purpose of this KKN activity is to answer the three problems that have been mentioned. The method of activity used is the lecture method, question and answer, and exercises (tutoring), socialization and practice methods (introduction to social media), as well as concept design and image recording (making videos of tourist objects). The results achieved were that several students were able to master the learning material provided, there were four social media accounts created for groups of woven craftsmen, and videos of tourist objects that had been created and distributed. It can be concluded that the implementation of the Field Work Lecture (KKN) that has been designed can run according to what has been planned and this activity is also able to answer several problems related to education, product marketing, and tourism.